Measuring Information System Project Success through a Software-Assisted Qualitative Content Analysis - Guo, Jin Xiu (Information Technology and Libraries, 2019)
Information System (IS)/IT project success is a growing interest in management due to its high impact on organizational change and effectiveness. Libraries have been adopting integrated library systems (ILS) to manage services and resources for years. It is essential for librarians to understand the mechanism of IS project management in order to successfully bring technology innovation to the organization. This study develops a theoretical model of measuring IS project success and tests it in an ILS merger project through a software-assisted qualitative content analysis. The model addresses project success through three constructs: (1) project management process, (2) project outcomes, and (3) contextual factors. The results indicate project management success alone cannot guarantee project success; project outputs and contextual factors also influence success through the leadership of the project manager throughout the lifecycle. The study not only confirms the proposed model in a post-project evaluation, but also signifies that project assessment can reinforce organizational learning, increase the chance of achieving success, and maximize overall returns for an organization. The qualitative content analysis with NVivo 11 has provided a new research method for project managers to self-assess an IS/IT project success systematically and learn from their experiences throughout the project lifecycle.